Complications Encountered with Total Hip Arthroplasty in Rheumatoid Patients - A. Aresti, Nick; S. Khan, Wasim; Malik, Atif (Current Rheumatology Reviews, 2015)
Rheumatoid arthritis affects around 1% of the global population with a predilection for Western societies. The treatment of the rheumatoid hip has gone through significant changes in recent years. Although osteotomies and synovectomies were previously commonplace, advances in arthroplasty technique and technology has seen these former procedures being performed less commonly. This article tackles some of the key issues with regard to the rheumatoid hip, namely the increased risk and methods of dealing with protrusio acetabuli, the risk of dislocation, infection and rates of aseptic loosening.
Keywords: infection